Empowering Karang Taruna Through Handicraft Production and Marketing as a Flagship of the Creative Economy - Junaidy, Junaidy; Merdayanty, Dewi; Subhan, Rizky; DA, Elisa Oktaviani; Anshari, Khairullah; Fadlun, Lukman; Azkiya, Farah (Abdimas Indonesian Journal, 2025)
This community service program aims to empower Karang Taruna RT 26 Sungai Ulin, Banjarbaru, by strengthening skills in producing and marketing handicraft products, particularly beaded bracelets, as part of the creative economy. Despite their potential, members face several obstacles, such as limited technical abilities, lack of entrepreneurial knowledge, restricted market access, and the absence of distinctive products. The program applies a participatory approach, engaging members directly in production training, entrepreneurship workshops, digital marketing strategies, and business management mentoring. The main targets include improving production skills among at least 80% of members, preparing a practical business management plan, and launching digital marketing with an initial goal of 100 bracelet sales within two months. Additional outcomes involve product design innovation, collaboration with local shops and online platforms, and increasing members’ income by 30% within six months. Overall, this program seeks to enhance youth economic independence while promoting sustainable, community-based creative economic growth in Sungai Ulin.